Zachowania konkurencyjne polskich przedsiębiorstw w warunkach ekspansji przedsiębiorstw zagranicznych na rynku polskim - Kałowski, Adam (The Competitive Behaviour of Polish Enterprises against the Foreign Rivals Expansion on Polish Market, 2008)
The conditions of functioning of Polish enterprises have deeply changed after Poland's joining the European Union. The integration process of Polish economy to the European one has enhanced foreign companies to invest and create their own entities on the Polish market. In these conditions Polish companies have to face a strong expansion of foreign companies on the Polish market. Within the last three years the foreign companies have invested almost 32% more than in 2004. Only within 2004-2006 the number of foreign entities grew by 14%. These data emphasize the level of foreign investments on the Polish market. To compete with foreign rivals Polish companies have to apply new competitive strategies. The research in this subject shows that the most used competitive strategy by Polish company is low cost company. The strategy of low cost company against the foreign rivals is not the best answer since Polish companies based their competitive advantages on low labour and raw materials cost and low exchange rate of own currency. Fortunately, a part of Polish businesses is aware of the risk and disadvantages of low cost strategy and is competing with foreign investors using differentiation. Moreover these companies have reached a success in competiting with foreign rivals. The paper presents a case study of Polish company Euro-Zoo which has faced a growing number of foreign rivals in its sector. Thanks to applied a differentiation strategy the company has grown rapidly and gained almost an oligopoly position in the whole sale of pet market. The presented case study is only one of many examples of Polish enterprises which have competed successfully with foreign rivals within last three years. Polish companies have gained knowledge how to compete and protect their own territory. Moreover their skills to adapt to a permanent change in their environments is a big advantage in a new situation. These two facts can be the base of future success of a Polish company.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 20, s. 139-149